Characteristics and Survival of 927 Moroccan Adults with Acute Myeloid Leukemia: Monocentric Experience - Ait boujmia, Oum kaltoum; Lamchahab, Mona; Hda, Nezha; Quessar, Asma (Asian Pacific Journal of Cancer Biology, 2021)
Acute myeloïd leukemia (AML) is the most frequent form of acute leukemia among adults and the most aggressive type of leukemia, which is associated with the lowest survival rate. Patients with AML are treated with intensive chemotherapy and many factors could influence the survival of these patients, such as age, cytogenetic abnormalities; white blood cell (WBC) counts. The aim of this work was to study the epidemiological and response profiles of AML adults patients in Morocco. Patients and Methods: A prospective, descriptive study conducted in the Hematology and Pediatric Oncology department, 20 August Hospital Casablanca, and concerned adult patients diagnosed with AML through a period of seven years (January 2011 to December 2017). Statistical analysis was performed using SPSS version 20. The overall survival and disease-free survival were evaluated by using the Kaplan–Meier method. Results: A total of 927 patients diagnosed with AML during the 7 year period. 466 (50.3%) were males and 461 (49.7%) were females. The median age of patients was 46years.The most represented age group was between 18 and 60 years old with a percentage of 83.2%.The FAB subtype M2 occurred most frequently (27%) followed by M1 (24.8%). The cytogenetic study showed that the majority of patients had a normal karyotype. The t (8; 21) was the most detected balanced translocation in our series and the intermediate cytogenetic group was the most represented group (65.4%). A total of 461 patients (53.54%) were treated according to the protocol AML11. The Disease-free survival (DFS) was significantly better for favorable cytogenetic group as compared to other cytogenetic groups (median survival of 41.58 months for the favorable group versus 29.07 months for the adverse group; p-value = 0.02). Conclusion: The age of AML patients was younger compared to other populations. The majority of patients had a normal karyotype and the commonest balanced translocation was the t (8; 21). Survival was higher in patients with good prognosis.